Hubungan Faktor Usia dan Gangguan Ovulasi dengan Kejadian Infertilitas Pada Wanita Usia Subur di Poli Klinik Kandungan Rumah Sakit EMC Pulomas - Irawati Sirait; Elfira Sri Futriani (Universitas Malahayati Lampung, 2024)
ABSTRACT Infertility in older women may be caused by the number and quality of eggs, or health problems that affect fertility. About 10-15% of couples facing infertility problems during their reproductive years experience ovulation disorders around 30-40% in infertile women. Based on the data above, I am interested in conducting research